Vertebral echinococcosis, its complications and death due to rupture of aorta. - Estrugo, Roberto L; Bueno, Marisa (Cirugía del Uruguay, 1976)
A young adult, from rural areas, was diagnos¡ed as a case of primitive vertebral echinococcosis by the authors and this was confirmed by the postmorten examination. He was brought to the hospital by reason of a complication: chronic renal failure due to compression of urinary tract. ClinicaJ data lead to establishing diagnosis: slow evolution, paraplegia and an abdominal mass. Radiological examination showed destruction of L4 and alterations in L3 and L5. Inmunoelectroforesis preved positive. Evolution !asted 26 years, the last six of which were characterized by the apearance of permanent paraplegia with sphincter incontinence and hydatid ossifluent pseudo-abscess. Obstructive renal failure was improved by means of a pyelonephrostomy and, at a second stage, drainage of ossifluent pseudoabscess. This patient died of a rare complication, hardly ever mentioned in bibliography: rupture of aort.a due to arteritis in the continuty of bone caries, after drainage of pseudo-abscess.